Improving Economics Education Student’s Interaction Ability in Business English Through a Task - Based Approach (Opinion Gap Activity) - Rozi, Fahrur; Oktarina, Nina (Fakultas Ekonomi, Universitas Negeri Semarang, 2018)
This research aims to find out the effectiveness of learning using a Task-Based Approach (Opinion-Gap Activity) in order to enhance student’s interaction and communication ability in Business English (Speaking Skills). This research analyzed 20 Bilingual Class students of Economics Education Department, Office Administration Education Study Program, Economics Faculty of Universitas Negeri Semarang (UNNES). This research was a class action research and implemented two cycles. The data collection technique used primary data and secondary data. The implementation of a Task-Based Approach (Opinion Gap Activity) in Business English learning is very effective for students in order to enhance the student’s interaction and communication ability in Business English. Then, this model of learning also increases students’ self-confidence when they communicate in English. In other words, student’s speaking skills in English is improved. In addition, it also enhances lecturer’s ability to manage Business English learning and enhances student’s activities and attention during learning process.